Betaine postpones hyperglycemia‐related senescence in ovarian and testicular cells: Involvement of RAGE and β‐galactosidase - Mohammadi, Neda; Hemmati, Mina; Motlagh, Behrouz; Biyabani, Arezou (Cell biochemistry and function, 2024)
The structural and functional disorders of the testis and ovary are one of the main complications of hyperglycemia. Betaine is a trimethyl glycine with antioxidant, antidiabetic, and anti‐inflammatory potential. The aim of this study is to investigate the potential of betaine on the expression of aging and oxidative stress markers in ovarian and testicular cells under hyperglycemic conditions. Testicular and ovarian cells were subjected to four different conditions, including normal glucose and hyperglycemia, with or without betaine (5 mM). The cells with hyperglycemia saw an increase in malondialdehyde (MDA), methylglyoxal (MGO), expression of a receptor for AGE, and aging‐related genes (β‐GAL), and a decrease in the activity of antioxidant enzymes including catalase, glutathione peroxidase, and superoxide dismutase. The treatment with betaine, in contrast, decreased the amount of MGO and MDA, and also downregulated aging‐related signaling. Although hyperglycemia induces senescence in testicular and ovarian cells, the use of betaine may have a protective effect against the cell senescence, which may be useful in the management of infertility. Significance statement This study identified that hyperglycemia had more noticeable effects in Leydig cells aging than granulosa cells, and that betaine, as a methyl group donor and an osmoprotectant, was able to improve these effects. These findings contribute to a better understanding of the aging process in the germ cells in response to hyperglycemia and also in the development of an effective management of infertility, notably in the male reproductive system.